Fast and green synthesis of an oligo-hydrocaffeic acid-based adhesive - Ali Ghadban (2020)
A green, mussel-inspired bioadhesive based on oligomerization of hydrocaffeic acid was synthesized in water by an ultrafast one-step reaction in the presence of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide as an activating agent. The resulting oligomers exhibited strong wet adhesion when applied to different substrates including glass, stainless steel, and aluminum. Compared to most commercial adhesives, this bioinspired adhesive is produced via a sustainable and green process, i.e., aqueous-based synthesis, one-step reaction, and in the absence of any purification step to obtain the final functional adhesive.